An Analysis of Feminist Criticism in The Lyrics of “The Man” Song by Taylor Swift - Amanda, Vina; Gumelar, Rizdki Elang; Riandi, Riandi (Journal of English Education Studies, 2024)
This research paper aims to find out the kinds of feminism and analyze the literal meaning of "The Man" Song by Taylor Swift. This research paper using a qualitative approach with a content analysis design. The data of this research is lyrics of “The Man” Song by Taylor Swift and the data was taken from YouTube. This research data collection using observation and documentation techniques. The finding of this research shows that there are 14 kinds of feminism which are divided into 5 psychoanalytic feminisms, 5 liberal feminisms, 2 Marxist feminisms and 2 radical feminisms. In The Man Song by Taylor Swift, a deep meaning is found in the representation of women's feelings of having to move quickly to match the steps of men. The women in the song feel that the world is too unfair for women who are considered weak creatures by the world in various aspects of life.